Handbook of computational quantum chemistry - Cook, David B. (Dover Publications, 2005)
This comprehensive text provides upper-level undergraduates and graduate students with an accessible introduction to the implementation of quantum ideas in molecular modeling, exploring practical applications alongside theoretical explanations. Topics include the Hartree-Fock method; matrix SCF equations; implementation of the closed-shell case; introduction to molecular integrals; and much more. 1998 edition.
Originally published: Oxford ; New York : Oxford University Press, 1998.
Keywords: Quantum chemistry -- Data processing.; elektronické knihy; electronic books